United States hegemony and the foundations of international law - Byers, Michael, 1966-; Nolte, Georg, 1959- (Cambridge University Press, 2003)
Leading scholars consider the effects of US hegemony on the international legal system. This book demonstrates that the effects of US predominance on the foundations of international law are real, but also intensely complex. Of interest to scholars of international law and international relations, government officials and international organisations.